IMPLIKASI PERBEDAAN GOOGLE TRANSLATE DAN KAMUS AL'ASHIRY DALAM PENGAJARAN PENDIDIKAN AGAMA ISLAM - WATI SUSIAWATI (Jurnal Pendidikan Islam, 2017)
Translation is an attempt to divert the meaning of the text (discourse) of the source language (lughah al-ashl) into the target language (al-lughah al-mustahdafah) or transfer the language of origin (source language, al-lughah al-mutarjam minha) into the target language (target language, al-lughah al-mutarjam ilaiha). The meaning of language is always associated with lafaz (Tenses), structure (Takrib), and context (Siyaq) circumstances. Meaning of words of a language can not be separated from the root word, appointment, and the context of its use. Therefore in 'ilm al-dilalah found at least nine theory of meaning, namely: Al-Nazariyah Al-Isyariyah, Al-Nazariyyah Al-Tashawwuriyyah, Al-Nazhariyyah Al-Sulukiyyah, Al-nazhariyyah al-siyaqiyyah, Al-nazhariyyah al -tahliliyyah, Al-nazhariyyah al-taulidiyyah, Al-nazhariyyah al-wadh'iyyah al-munthiqiyyah fi al-meaning, Al-nazhariyyah moore-Quine, in the process of translation, a translator needs to pay attention to some basic elements in translating both language elements and non-language. The aim of  Research is to compare the  result of two different data translatios from  google translate and al ashiry Arabic dictionary. The results showed that 40% of google translation results are not as they should be according to the Urn dalalah theory.